2004
DOI: 10.1103/physreva.69.042714
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization cross sections of O II, O III, O IV, and O V: BenchmarkingR-matrix theory and experiments

Abstract: For crucial tests between theory and experiment, ab initio close-coupling calculations are carried out for photoionization of several oxygen ions: O II, O III, O IV, and O V. The relativistic fine-structure and resonance effects are studied using the R matrix and its relativistic variant, the Breit-Pauli R-matrix (BPRM) approximations. Extremely detailed comparison is made with high-resolution experimental measurements carried out in three different setups: Advanced Light Source at Berkeley, synchrotron radiat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Although this does not guarantee complete resolution and the OP cross sections may still be under-resolved for certain applications such as monochromatic spectral modelling, they are considerably better than those with constant energy mesh. The new results reported in this work are obtained as in the recent calculations for a number of oxygen ions, O II-O V, using a more extensive eigenfunction expansion for the target ion than in the OP work; they are in good detailed agreement with recent experimental measurements (Nahar 2004). Extensive resonance structures are delineated, especially in the near-threshold region.…”
Section: Photoionization Cross Sections and Ratessupporting
confidence: 73%
See 2 more Smart Citations
“…Although this does not guarantee complete resolution and the OP cross sections may still be under-resolved for certain applications such as monochromatic spectral modelling, they are considerably better than those with constant energy mesh. The new results reported in this work are obtained as in the recent calculations for a number of oxygen ions, O II-O V, using a more extensive eigenfunction expansion for the target ion than in the OP work; they are in good detailed agreement with recent experimental measurements (Nahar 2004). Extensive resonance structures are delineated, especially in the near-threshold region.…”
Section: Photoionization Cross Sections and Ratessupporting
confidence: 73%
“…Nevertheless, R-matrix calculations for photoionization cross sections have been experimentally verified, some computed in LS coupling prior to experiments. For example, we note the extremely detailed comparison between R-matrix cross sections and recent experiments on synchrotron based light sources reported by the Reno/Berkeley group for O II (Covington et al 2001), the Aarhus group for C II (Kjeldsen et al 1999, Nahar 2002) and the Paris group for O ions (Champeaux et al 2003, Nahar 2004). Near-threshold resonances need to be carefully resolved, often with relativistic fine structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The R-matrix results (middle panels) are from Fernley et al (1999, from the Opacity Project) and Nahar & Pradhan (1997), with additional data for O 3+ in Fig. 5 by Nahar (1998Nahar ( , 2004 The experimental spectra show different resonances superimposed on decreasing continua and exhibit marked differences along the series N 2+ -F 4+ . A continuous decrease of the continuum cross section is observed going through the series while the ionization threshold increases.…”
Section: Resultsmentioning
confidence: 97%
“…Employing the same method, Nahar & Pradhan (1997) calculated the cross sections of the ions of C, N, and O (including N 2+ and O 3+ ) as part of the Iron Project, and later Nahar (1998) reported details of the calculations for oxygen and its ions. All the above investigations were non-relativistic, but after that experiments had demonstrated that such an approach was insufficient to describe the spectrum of C + (Kjeldsen et al 1999a), R-matrix calculations including relativistic effects have been carried out for oxygen ions (Nahar 2004; see also Champeaux et al 2003).…”
Section: Resultsmentioning
confidence: 99%